Public-Private Partnership as Innovative Form of Attraction of Financial Resources in Sphere of Tourism - NOVOLODSKAYA, Galina Ivanovna; KRAMAROVA, Tatyana Yuryevna; LEBEDEV, Kostyantyn Anatol'evich; PONKRATOVA, Liudmila Alekseevna; CHICHEROVA, Elena Yuryevna (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
The paper is devoted to the development of approaches to realisation of public-private partnership (PPP) in the sphere of tourism. It has been proved that it is expedient to concentrate on a narrower economic understanding of PPP in the tourist industry. It has been established that it is necessary to regulate authorities, forms of relationships, to share risks, to provide legal guarantees on repayment of funds in the framework of PPP in the sphere of tourism. It has been determined that it is necessary to pick out a coordinating body, which will inform potential participants about peculiarities of projects’ realisation, as well as render educational services on the problematics of PPP, take part in competitions on selecting participants. It is proposed to foresee mechanisms of providing state guarantees on attracting financial resources and an opportunity of granting privileges to private investors in the framework of PPP in the sphere of tourism.